MSME Accounting Training and Assistance for Micro, Small and Medium Enterprises (MSMEs) to Improve Company Financial Performance in Kampar Regency - Humairoh, Fitri; Yusralaini, Yusralaini; Nurulita, Suci; Aprina, Diana; Gustiani, Natasha Fahira (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2024)
This community service activity aims to provide accounting training and assistance to Micro, Small and Medium Enterprises (MSMEs) in Kampar Regency, in order to improve their financial performance. The training, which was held on October 16, 2024, included basic accounting materials, recording transactions, and preparing financial statements in accordance with the Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM). The results of this activity showed that the majority of participants experienced an increased understanding of the importance of accounting and were able to prepare simple financial statements. Although there are challenges in applying the knowledge gained, this activity shows great potential to improve the financial performance of MSMEs in the area. With the knowledge gained, it is expected that MSME players can be more independent in managing their finances and contribute to the local economy.